THE INFLUENCE OF PARTICIPATIVE LEADERSHIP STYLE OF COMMUNITY RELATIONS OFFICER PT. HOLCIM INDONESIA TBK. CILACAP-PLANT ON THE PERFORMANCE OF POSDAYA COMMUNITIES IN SUB-DISTRIC OF NORTH CILACAP - Cahyani, Riyas Anggun Putri (Komuniti: Jurnal Komunikasi dan Teknologi Informasi, 2015)
The application of management aspects by a CRO to complete empowerment activities can be?done by a work style which tends to lead to participative leadership. The leadership components?consists of consultation, joint decision making, power sharing, decentralization, empowerment,?democratic management tested to see the effects on the community empowerment program fromPT. Holcim Indonesia Tbk. Cilacap. PT. Holcim Indonesia Cilacap Tbk. is one of the companies who?received many awards related to successful of their performance community development as aform empowerment of local communities, that is Posdaya (Family Empowerment Program).?This study aims to examine and analyze the influence of participative leadership style of the?Community Relations Officer (CRO) PT. Holcim Indonesia Tbk Cilacap - Plant toward Posdaya (Family Empowerment Centre) in North Cilacap. This study uses quantitative methods and the data collected by the distribution of questionnaires which consist as 96 samples. It was measured by using?slovin formulate with a degree of error is 5 % for 126 communities. The research was used proportional sampling as a sampling technique and analyzed by SPSS for windows 16.00, include validity?and reliability tests to examine the questionnaires. t-test, F-test and coefficient of determination?(R2) were the part of a simple regression analysis to prove the hypothesis of the research. Based?on the data analysis, the simple linear regression equation is Y = 11.370 + 0,423X, its means that?there was a linearly and positively influence of participative leadership style on the performance?of Posdaya communities. The conclusion is if participative leadership style of the CRO is increased,?the performance of Posdaya will also increase.